Biofabrication: Biofabrication Using Electrochemical Devices and Systems (Adv. Biosys. 4/2020). Issue 4 (14th April 2020) - Ino, Kosuke; Ozawa, Fumisato; Dang, Ning; Hiramoto, Kaoru; Hino, Shodai; Akasaka, Rise; Nashimoto, Yuji; Shiku, Hitoshi
Abstract : In article number 1900234, Kosuke Ino, Hitoshi Shiku, and co‐workers describe recent advances in applying electrochemical devices/systems for biofabrication. They review the electrodeposition of hydrogels and conductive materials for 3D cell culture, electrochemical modification of culture surfaces, and cell aggregation using electrochemical devices and electrochemical stimulation methods. Finally, future research directions in this field and the application prospects are highlighted.